PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS LITERASI SAINS PADA MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Nisa, Nova Khoirun; Natalina, Mariani; Suwondo, Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to develop the Student Worksheet (LKPD) based onscience literacy for seniorhigh school gradeX of the topic of biodiversityin April-December 2019. The research was conducted in twoplaces, namely to Strudent Worksheetvalidation was conducted at the FKIP UNRI Biology Education Campus and Student Worksheetlimited trials were conducted at SMAN 1 Pekanbaru. This type of research refers to the R&D research approach using the ADDIE model developed by Dick and Carry. The subject of this research is the subject matter of Biology inseniorhigh school gradeX KD 3.2. The developed LKPD consisted of3meetings with a time allocation of 1 meetingfor 45 minutes. The parameters of this study include the results of the validation of the development of student worksheetby the validatorand respon assesment by student. The assessment is doing withvalidation sheet and a questionnaire. Data analysis is descriptive qualitative and quantitative. The results of this study indicate that student worksheetthat have been developed are in the very valid category with an average score of all aspects of 3.53. The value of the answers to all aspects the valueof the results of a limited trial phase I and stage II in all aspects obtained an average score of 3.39 with a very good category. Based on the results of the validation, the results of the first trial, the results of the second trial and the revisions that have been made,student worksheet is good and feasible to be used as a reference at school learning to increase students knowledge and understanding for the topic of biodiversity.KeyWords: Student Worksheets, Science Literacy, Biodiversity